A new flexible extension of the Lindley distribution with applications - Adel Alrasheedi (Elsevier, 2022)
A new general family of distributions based on the Lindley model was introduced. Some properties of the proposed model, including moments, quantiles, and order statistics are presented. In addition, some reliability measures of this model were investigated. The parameters were estimated using the moments and the maximum likelihood methods for complete and right-censored data. Then, the behavior of the maximum likelihood estimator was investigated in a simulation study. Finally, the model was applied to the analysis of two data sets to demonstrate its usefulness.